Dicarboxylic esters: Useful tools for the biocatalyzed synthesis of hybrid compounds and polymers - Bassanini, Ivan; Hult, Karl; Riva, Sergio (Beilstein Journal of Organic Chemistry, 2015)
Dicarboxylic acids and their derivatives (esters and anhydrides) have been used as acylating agents in lipase-catalyzed reactions in organic solvents. The synthetic outcomes have been dimeric or hybrid derivatives of bioactive natural compounds as well as functionalized polyesters.
Keywords: biocatalysis; dicarboxylic acids; lipase; polyesters; regioselectivity

Organic Synthesis with Enzymes in Non-Aqueous Media - Carrea, G.; Riva, S. (Wiley-VCH, 2008)

Enzymatic Reations in Organic Media - Koskinen, A. M. P.; Klibanov, A. M. (Chapman & Hall, 1996)

(untitled) - Klibanov, A. M. (Nature, 2001)

(untitled) - Klibanov, A. M. (Trends Biochem. Sci., 1989)

(untitled) - Park, S.; Kazlauskas, R. J. (Curr. Opin. Biotechnol., 2003)

(untitled) - Carrea, G.; Riva, S. (Angew. Chem., Int. Ed., 2000)

(untitled) - Plou, F. J.; Cruces, M. A.; Ferrer, M.; Fuentes, G.; Pastor, E.; Bernabè, M.; Christensen, M.; Comelles, F.; Parra, J. L.; Ballesteros, A. (J. Biotechnol., 2002)

(untitled) - Therisod, M.; Klibanov, A. M. (J. Am. Chem. Soc., 1986)

(untitled) - Cruz Silva, M. M.; Carvalho, J. F.; Riva, S.; Sà e Melo, M. L. (Curr. Org. Chem., 2011)

(untitled) - Michels, P. C.; Khmelnitsky, Y. L.; Dordick, J. S.; Clark, D. S. (Trends Biotechnol., 1998)

(untitled) - Akbar, U.; Shin, D.-S.; Schneider, E.; Dordick, J. S.; Clark, D. S. (Tetrahedron Lett., 2010)

(untitled) - Secundo, F.; Carrea, G.; De Amici, M.; Joppolo di Ventimiglia, S.; Dordick, J. S. (Biotechnol. Bioeng., 2003)

(untitled) - Kirchner, G.; Scollar, M. P.; Klibanov, A. M. (J. Am. Chem. Soc., 1985)

(untitled) - Riva, S.; Chopineau, J.; Kieboom, A. P. G.; Klibanov, A. M. (J. Am. Chem. Soc., 1988)

(untitled) - Faber, K.; Riva, S. (Synthesis, 1992)

(untitled) - Magrone, P.; Cavallo, F.; Panzeri, W.; Passarella, D.; Riva, S. (Org. Biomol. Chem., 2010)

(untitled) - Bianchi, D.; Cesti, P.; Battistel, E. (J. Org. Chem., 1988)

(untitled) - Ottolina, G.; Carrea, G.; Riva, S. (Biocatalysis, 1991)

(untitled) - Schrittwieser, J. H.; Resch, V. (RSC Adv., 2013)

(untitled) - Serra, S.; Fuganti, C.; Brenna, E. (Trends Biotechnol., 2005)

(untitled) - Sima Sariaslani, F.; Rosazza, J. P. N. (Enzyme Microb. Technol., 1984)

(untitled) - González-Sabín, J.; Morán-Ramallal, R.; Rebolledo, F. (Chem. Soc. Rev., 2011)

(untitled) - Riva, S. (J. Mol. Catal. B: Enzym., 2001)

WO Patent - Nunez, L. E.; Menendez, N.; Gonzalez-Sabin, J.; Moris-Varas, F.; Garcia-Fernandez, B.; Perez, M.; Brana, V.; Salas, J. A. (2011)

(untitled) - Xiao, Y. M.; Mao, P.; Zhao, Z.; Yang, L. R.; Lin, X. F. (Chin. Chem. Lett., 2010)

(untitled) - Danieli, B.; Luisetti, M.; Riva, S.; Bertinotti, A.; Ragg, E.; Scaglioni, L.; Bombardelli, E. (J. Org. Chem., 1995)

(untitled) - Riva, S.; Danieli, B.; Luisetti, M. (J. Nat. Prod., 1996)

(untitled) - Krejzová, J.; Šimon, P.; Vavříková, E.; Slámová, K.; Pelantová, H.; Riva, S.; Spiwok, V.; Křen, V. (J. Mol. Catal. B: Enzym., 2013)

(untitled) - Vavrivoka, E.; Vack, J.; Valentova, K.; Marhol, P.; Ulrichova, J.; Kuzma, M.; Kren, V. (Molecules, 2014)

(untitled) - Khmelnitsky, Y. L.; Budde, C.; Arnold, J. M.; Usyatinsky, A.; Clark, D. S.; Dordick, J. S. (J. Am. Chem. Soc., 1997)

(untitled) - Wu, Q.; Xia, A.; Lin, X. (J. Mol. Catal. B: Enzym., 2008)

(untitled) - Xia, A.; Wu, Q.; Liu, B.; Lin, X. (Enzyme Microb. Technol., 2008)

(untitled) - Quian, X.; Liu, B.; Wu, Q.; Lv, D.; Lin, X.-F. (Bioorg. Med. Chem., 2008)

(untitled) - Quan, J.; Chen, Z.; Han, C.; Lin, X. (Bioorg. Med. Chem., 2007)

(untitled) - Wu, Q.; Wang, M.; Chen, Z. C.; Lu, D. S.; Lin, X. F. (Enzyme Microb. Technol., 2006)

(untitled) - Romeo, S.; Parapini, S.; Dell’Agli, M.; Vaiana, N.; Magrone, P.; Galli, G.; Sparatore, A.; Taramelli, D.; Bosisio, E. (ChemMedChem, 2008)

(untitled) - Passarella, D.; Giardini, A.; Peretto, B.; Fontana, G.; Sacchetti, A.; Silvani, A.; Ronchi, C.; Cappelletti, G.; Cartelli, D.; Borlak, J.; Danieli, B. (Bioorg. Med. Chem., 2008)

(untitled) - Ayral-Kaloustian, S.; Gu, J.; Lucas, J.; Cinque, M.; Gaydos, C.; Zask, A.; Chaudhary, I.; Wang, J.; Di, L.; Young, M.; Ruppen, M.; Mansour, T. S.; et al. (J. Med. Chem., 2010)

(untitled) - Riva, E.; Comi, D.; Borrelli, S.; Colombo, F.; Danieli, D.; Borlak, J.; Evensen, L.; Lorens, J. B.; Fontana, G.; Gia, O. M.; Via, L. D.; Passarella, D. (Bioorg. Med. Chem., 2010)

(untitled) - Passarella, D.; Peretto, B.; Blasco y Yepes, R.; Cappelletti, G.; Cartelli, D.; Ronchi, C.; Snaith, J.; Fontana, G.; Danieli, B.; Borlak, J. (Eur. J. Med. Chem., 2010)

(untitled) - Passarella, D.; Comi, D.; Cappelletti, G.; Cartelli, D.; Gertsch, J.; Quesada, A. R.; Borlak, J.; Altmann, K.-H. (Bioorg. Med. Chem., 2009)

(untitled) - Danieli, B.; Giardini, A.; Lesma, G.; Passarella, D.; Peretto, B.; Sacchetti, A.; Silvani, A.; Pratesi, G.; Zunino, F. (J. Org. Chem., 2006)

(untitled) - Passarella, D.; Comi, D.; Vanossi, A.; Paganini, G.; Colombo, F.; Ferrante, L.; Zuco, V.; Danieli, B.; Zunino, F. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Ambrosi, M.; Fratini, E.; Alfredsson, V.; Ninham, B. W.; Giorgi, R.; Lo Nostro, P.; Baglioni, P. (J. Am. Chem. Soc., 2006)

(untitled) - Dolle, C.; Magrone, P.; Riva, S.; Ambrosi, M.; Fratini, E.; Peruzzi, N.; Lo Nostro, P. (J. Phys. Chem. B, 2011)

(untitled) - Sahoo, B.; Brandstat, K. F.; Lane, T. H.; Gross, R. A. (Org. Lett., 2005)

(untitled) - Okumura, S.; Iwai, M.; Tominaga, Y. (Agric. Biol. Chem., 1984)

(untitled) - Zhang, J.; Shi, H.; Di Wu, D.; Xing, Z.; Zhang, A.; Yang, Y.; Li, Q. (Process Biochem., 2014)

(untitled) - Kobayashi, S.; Makino, A. (Chem. Rev., 2009)

(untitled) - Gross, R. A.; Ganesh, M.; Lu, W. (Trends Biotechnol., 2010)

(untitled) - Vouyiouka, S. N.; Topakas, E.; Katsini, A.; Papaspyrides, C. D.; Christakopoulos, P. (Macromol. Mater. Eng., 2013)

(untitled) - Binns, F.; Harffey, P.; Roberts, S. M.; Taylor, A. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Kulshrestha, A. S.; Gao, W.; Gross, R. A. (Macromolecules, 2005)

(untitled) - Yang, Z.; Zhang, X.; Luo, X.; Jiang, Q.; Liu, J.; Jiang, Z. (Macromolecules, 2013)

(untitled) - Bhatia, S.; Mohr, A.; Mathur, D.; Parmar, V. S.; Haag, R.; Prasad, A. K. (Biomacromolecules, 2011)

(untitled) - Liu, B.; Zhang, X.; Chen, Y.; Yao, Z.; Yang, Z.; Gao, D.; Jiang, Q.; Liu, J.; Jiang, Z. (Polym. Chem., 2015)

(untitled) - Wallace, J. S.; Morrow, C. J. (J. Polym. Sci., Part A-1: Polym. Chem., 1989)

(untitled) - Yang, Y.; Lu, W.; Cai, J.; Hou, Y.; Ouyang, S.; Xie, W.; Gross, R. A. (Macromolecules, 2011)

(untitled) - Warwel, S.; Demes, C.; Steinke, G. (J. Polym. Sci., Part A-1: Polym. Chem., 2001)

(untitled) - Jiang, Y.; Woortman, A. J. J.; van Ekenstein, G. O. R. A.; Loos, K. (Biomolecules, 2013)

(untitled) - Yao, D.; Li, G.; Kuila, T.; Li, P.; Kim, N. H.; Kim, S.-I.; Lee, J. H. (J. Appl. Polym. Sci., 2011)

(untitled) - Kato, M.; Toshima, K.; Matsumura, S. (Biomacromolecules, 2009)

(untitled) - Tanaka, A.; Kohri, M.; Takiguchi, T.; Kato, M.; Matsumura, S. (Polym. Degrad. Stab., 2012)

(untitled) - Khan, A.; Sharma, S. K.; Kumar, A.; Watterson, A. C.; Kumar, J.; Parmar, V. S. (ChemSusChem, 2014)

(untitled) - Pandey, M. K.; Kumar, S.; Thimmulappa, R. K.; Parmar, V. S.; Biswal, S.; Watterson, A. C. (Eur. J. Pharm. Sci., 2011)

(untitled) - Pandey, M. K.; Kumar, A.; Ravichandran, S.; Parmar, V. S.; Watterson, A. C.; Kumar, J. (J. Macromol. Sci., Part A: Pure Appl. Chem., 2014)

(untitled) - Frampton, M. B.; Séguin, J. P.; Marquardt, D.; Harroun, T. A.; Zelisko, P. M. J. (J. Mol. Catal. B: Enzym., 2013)

(untitled) - Müller, S. S.; Frey, H. (Macromol. Chem. Phys., 2012)

(untitled) - Liu, J.; Jiang, Z.; Zhou, J.; Zhang, S.; Saltzman, W. M. (J. Biomed. Mater. Res., Part A, 2011)

(untitled) - Qian, X.; Jiang, Z.; Lin, X.; Wu, Q. (J. Polym. Sci., Part A-1: Polym. Chem., 2013)

(untitled) - Qian, X.; Wu, Q.; Xu, F.; Lin, X. (Polymer, 2011)

(untitled) - Xu, F.; Zhong, J.; Qian, X.; Li, Y.; Lin, X.; Wu, Q. (Polym. Chem., 2013)

(untitled) - Ragupathy, L.; Ziener, U.; Dyllick-Brenzinger, R.; von Vacano, B.; Landfester, K. (J. Mol. Catal. B: Enzym., 2012)

(untitled) - Poulhès, F.; Mouysset, D.; Gil, G.; Bertrand, M. P.; Gastaldi, S. (Polymer, 2013)

(untitled) - Syrén, P.-O. (FEBS J., 2013)

(untitled) - Uyama, H.; Kikuchi, H.; Kobayashi, S. (Bull. Chem. Soc. Jpn., 1997)

(untitled) - Eriksson, M.; Hult, K.; Malmström, E.; Johansson, M.; Trey, S. M.; Martinelle, M. (Polym. Chem., 2011)

(untitled) - Eriksson, M.; Boyer, A.; Sinigoi, L.; Johansson, M.; Malmström, E.; Hult, K.; Trey, S.; Martinelle, M. (J. Polym. Sci., Part A-1: Polym. Chem., 2010)

(untitled) - Eriksson, M.; Fogelström, L.; Hult, K.; Malmström, E.; Johansson, M.; Trey, S.; Martinelle, M. (Biomacromolecules, 2009)